Análise qualitativa e comparativa das variáveis morfométricas da região serrana da porção Sul do Maciço Central do Ceará geradas através dos MDE: SRTM, ASTER GDEM e TOPODATA - Carmo, Alcione Moreira do (2022)
With the advancement of computer technology in recent decades came along the advancement of digital data and the ease of obtaining this information gathering from the World Wide Web. Digital models of ground elevations, for example, which generated data of complex and difficult access some years ago, are now available freely on the internet in different resolutions and accuracies for the entire globe. Many works developed in the scientific community use digital elevation models (DEM) for various types of analyses which are interested in searching, but few heeded to verify the quality of data and products obtained through these models which could indicate the best one for a particular type of analysis or may exhibit a better result for a given working range. Based on these questions, this study was designed to make a qualitative and comparative analysis of the three more available DEM (ASTER-GDEM, SRTM, and TOPODATA) on the internet, where they underwent a series of processes in a GIS environment to extract and analyze numerous geomorphological and hydrological variables such as land slope, the slope aspect and the profile and plan curvature at three different scales. For this, a pilot area located in the mountains of the South portion of the Central Massif from the State of Ceará, more precisely located between the cities of Acopiara, Mombaça, and Piquet Carneiro was defined. The results obtained by means of qualitative and comparative analysis among the three types of MDE generated different answers from each other, primarily in relation to the spatial resolution of the data, which reflects greater or lesser details of the morphology of the terrain, as well as in highlighting the lines and directions of flows by the horizontal and vertical curves obtained for each analyzed scale.